2019
DOI: 10.1021/acssuschemeng.9b03205
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured ZSM-11 Catalyst on Stainless Steel Microfibers for Improving Glycerol Dehydration to Acrolein

Abstract: Glycerol is a byproduct from the biodiesel manufacturing. Glycerol dehydration into more valuable acrolein is desirable and essential since it improves the economics of the biodiesel production and offers a sustainable route to replace the market favorite chemical from petroleum process. Zeolites with the dominant Brønsted acid sites have been wildly used in glycerol dehydration, since Brønsted acid sites are flexible and interacting with the center hydroxyl of glycerol towards acrolein production. In this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It is well-known that there are two main competing routes in the dehydration of glycerol: (i) formation of acrolein on Brønsted acid sites and (ii) formation of acetol on Lewis acidic sites (Scheme 3). The mechanisms of acrolein and acetol formation on these sites were first proposed by Alhanash et al [16] who used Cs 2.5 H 0.5 PW 12 O 40 as a catalyst and then confirmed by many authors using metal oxides, [17,18] zeolites, [19,20] metal phosphides, [21] and HPAs. [22] In general, the dehydration of glycerol on Brønsted acid sites starts with the protonation of the secondary oxygen atom which has a higher negative charge compared to the terminal oxygen atoms (Scheme 3a).…”
Section: Type Of Acid Sitesmentioning
confidence: 91%
“…It is well-known that there are two main competing routes in the dehydration of glycerol: (i) formation of acrolein on Brønsted acid sites and (ii) formation of acetol on Lewis acidic sites (Scheme 3). The mechanisms of acrolein and acetol formation on these sites were first proposed by Alhanash et al [16] who used Cs 2.5 H 0.5 PW 12 O 40 as a catalyst and then confirmed by many authors using metal oxides, [17,18] zeolites, [19,20] metal phosphides, [21] and HPAs. [22] In general, the dehydration of glycerol on Brønsted acid sites starts with the protonation of the secondary oxygen atom which has a higher negative charge compared to the terminal oxygen atoms (Scheme 3a).…”
Section: Type Of Acid Sitesmentioning
confidence: 91%
“…The catalysts were developed and optimized to exhibit high water tolerance. It was shown that in addition to decreasing the viscosity of the feed, the presence of large amounts of water was essential to promote the formation of acrolein in high selectivity and inhibit the formation of carbonaceous deposits on the catalyst. …”
Section: Upgrading Of Polyolsmentioning
confidence: 99%
“…A plethora of catalysts were prepared and evaluated in gas-phase fixed-bed flow reactor, such as zeo­lites and molecular sieves, hetero­poly acids, ,,, niobium-based, ,, vanadium-based, , tungsten-based, ,,,, ,,, and other transition metal-based…”
Section: Upgrading Of Polyolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are phenol, dihydrofuran, cyclopentanone, methylcyclopentenone, cyclohexenone, tetrahydropyran-2-carbaldehyde and 2-oxepanone. [10,28,77,82,83] Such compounds are obtained mainly through oligomerization (aldol condensation) reactions from oxygenated products and intermediates, in which oxygen is removed in the form of water. [65,78,79] Afterward, these compounds are converted to aromatics from multiple steps of oligomerization, cyclization, dehydration, dehydrogenation, H-transfer, alkylation and other reactions.…”
Section: Formation Of Carbonaceous Compounds Throughout the Reaction On The H-zsm-5 Zeolitementioning
confidence: 99%